Potential Donor Families' Experiences of Organ and Tissue Donation–related Communication, Processes and Outcomes. Issue 1 (January 2016) - Marck, C. H.; Neate, S. L.; Skinner, M.; Dwyer, B.; Hickey, B. B.; Radford, S. T.; Weiland, T. J.; Jelinek, G. A.
We aimed to describe the experiences of families of potential organ and tissue donors eligible for donation after circulatory death or brain death. Forty-nine family members of potential donors from four Melbourne hospitals were interviewed to assess their experiences of communication, processes and the outcomes of donation. Interviews were recorded, transcribed verbatim and analysed thematically. Families expressed a range of perspectives on the themes of communication, hospital processes and care, the processes of consent and donation and reflected on decisions and outcomes. They expressed satisfaction overall with communication when receiving bad news, discussing death and donation. Honest and frank communication and being kept up-to-date and prepared for potential outcomes were important aspects for families, especially those of post circulatory death donors. Participants reported high levels of trust in healthcare professionals and satisfaction with the level of care received. Many donor families indicated the process was lengthy and stressful, but not significantly enough to adversely affect their satisfaction with the outcome. Both the decision itself and knowing others' lives had been saved provided them with consolation. No consenting families, and only some non-consenting families, regretted their decisions. Many expressed they would benefit from a follow-up opportunity to ask questions and clarify possible misunderstandings. Overall, while experiences varied, Australian families valued frank communication, trusted health professionals, were satisfied with the care their family member received and with donation processes, despite some apparent difficulties. Family satisfaction, infrequently assessed, is an important outcome and these findings may assist education for Australian organ donation professionals.